Reconnect : building school culture for meaning, purpose, and belonging - Lemov, Doug, 1967-; Lewis, Hilary (Educational consultant); Williams, Darryl (Educational consultant); Frazier, Denarius (Jossey-Bass, 2023)
"The book begins by defining the problem: The (screen) epidemic-fed-pandemic has students struggling without a sense of belonging and community. Therefore, a good school should set out to rebuild a sense of community for its students. Adults and school systems communicate belonging, but peer-to-peer interactions are perhaps most important. Schools must have a theory about what peer-to-peer interactions most affect students' sense of belonging, and they must be willing to play an active role in shaping it. However, belonging' involves both respect for individual identity but also a shared sense of group identity. This attitude is increasingly at odds with how we see society-it defends individual rights, but it has less and less of a sense of collective obligation. Shared values define us and build academic rigor. There is a hidden curriculum that schools teach. Good schools teach intellectual virtues, moral virtues, civic virtues and performance virtues. Teaching students how to be successful contributors to shared endeavor and community how to be connected to things that are greater than the sum of the individual parts is essential to making productive and happy citizens. Reconnect provides practical solutions for rebuilding community, structure, and a sense of belonging in schools"--